The world upside down – after 20 years follow-up of dextro-transposition of the great arteries. (14th October 2021) - Alves Pinto, R; Martins Carvalho, M; Proenca, T; Torres, S; Grilo, P D; Resende, C X; Calvao, J; Costa, C; Amador, A F; Marques, C; Cabrita, A; Cruz, C; et al.
Abstract: Introduction: Congenital Heart Disease (CHD) affects under 1% of newborns and thanks to its prognosis improvement, most patients survive until adulthood. Dextro-transposition of the great arteries (dTGA) is a CHD classically palliated with atrial switch (ATS) procedure and nowadays corrected with an arterial switch (ARS), with better clinical outcomes. Nevertheless, several post-ATS patients remain alive and questions persist regarding their long-term prognosis. Purpose: To observe a group of dTGA patients followed in an Adult CHD outpatients clinic, access their comorbidities, surgical interventions, complications and clinical outcomes. Methods: We retrospectively analyzed a group of dTGA patients born between 1974 and 2001. Clinical features were collected and time-to-event statistics were analyzed. Adverse event was defined as at least one of the follows: death, stroke, myocardial infarction or coronary revascularization, arrhythmia and ventricular, valvular or conduct dysfunction. Results: A total of 80 patients were enrolled with a mean follow-up of 26 years after surgery: 46% were female, median age 27 (19–57) year-old. Concerning other concomitant defects, 25% had ventricular septal defect, 12% pulmonary stenosis, 3% aortic coarctation and 1% single coronary ostium. ATS palliation was performed in 54% of patients (Senning procedure in 95%) and ARS (Jatene procedure) in 45% of patients; median age at procedure was 13 months and 10 days, respectively. During follow-up, almost all patients submitted to ARS remained in sinus rhythm (97%) versus 64% of ATS patients (p=0.037). The latter group had higher incidence of arrythmias (40% vs 3%, p=0.013), mostly atrial flutter or fibrillation (present in 28%), followed by bradyarrhythmia (10%); median time from surgery to first arrhythmic event in these patients was 23 years. Also, systemic ventricle systolic dysfunction (SVSD) and chronotropic incompetence were significantly higher in ATS (41% vs 3%, p<0.001 and 46% vs 9%, p=0.005, respectively); mean time to SVSD was 29 years. In respect to long-term outcomes in ARS, the most frequent complications were moderate to severe aortic regurgitation, pulmonary stenosis and regurgitation, occurring in 21%, 7% and 3%, respectively. Concerning both groups, mean time to first adverse-event was 21 years. Regarding gender and demographic features, there were no differences in time-to-adverse-event, comparing patients living in urban versus rural neighbourhoods and female versus male (Log Rank, p=0.368 and p=0.693). Only one patient died, submitted to ATS, at 46 years-old, from chronic heart failure. Conclusion: After a long-term free of events, ATS patients experienced more arrhythmic complications and SVSD. ARS complications were anastomosis related. This report highlights the efforts that should be made to identify late complication is this particular population. Of note, no demographic or gender differences were observed. Funding Acknowledgement: Type of funding sources: None.